Problem rozmieszczenia maszyn liczących w dużych systemach przemysłowych automatycznie sterowanych - Kulik, Czesław (Wydział Prawa i Administracji UAM, 1974)
The author deals with the methods of choice of the optimal location of points on the basis of linear graphs. He has also proposed an algorithm which may be aeasily programmed and used with the help of a computer.